The Karabakh War and Ethnic Cleaning through the Eyes of Witness and Researcher - Ahanchi, Parvin (Genocidas ir rezistencija, 2024)
This article is based on eyewitness testimonies regarding the ethnic cleansing practices carried out by Armenian ultranationalists against ethnic Azerbaijanis during the Karabakh conflict (Nagorno–Karabakh conflict) and the First Karabakh War (1988–1994). Since 1988, ethnic cleansing has been a prevalent form of violence directed at ethnic Azerbaijanis, resulting in the forcible displacement of approximately one million individuals from the Karabakh region and Armenia. The paper examines the Karabakh conflict and ethnic cleansing through oral testimonies, which provide substantial evidence of atrocities committed against Azerbaijanis. These atrocities have deep historical roots, marked by violent ethnic conflicts, such as the Armenian–Muslims massacres of 1905 and 1918, and the widespread terror inflicted by Armenian chauvinists on Azerbaijani populations. These incidents involved the systematic targeting and destruction of Azerbaijani villages, culminating in severe acts of violence and genocide in the South Caucasus between 1917 and 1921. The events were marked by large-scale ethnic violence and mass killings, resulting in widespread loss of life and deepening tensions between the Armenian and Azerbaijani communities. These events left lasting scars on the region and intensified ethnic and territorial conflicts that shaped subsequent historical developments. This paper also addresses a lesser-known aspect of the Nagorno–Karabakh conflict: the helicopter crash that resulted in the deaths of 44 passengers, primarily women and children, and 3 crew members. This article brings to light the human and environmental catastrophes resulting from the ethnic cleansing and terror acts committed during the Karabakh conflict. Incorporating Azerbaijani eyewitness testimonies and a historical analysis of Armenian media disinformation highlights the critical need to confront these atrocities as part of a path toward justice and reconciliation.
Keywords: Karabakh conflict and ethnic cleansing; Armenian terror acts; crimes against humanity; collective trauma; collective memory